Effects of Using Thinking Routines on the Academic Results of Business Students at a Chilean Tertiary Education Institution. (12th November 2019) - Sepulveda Larraguibel, Yerko; Venegas‐Muggli, Juan I.
ABSTRACT: The present study investigates the effects of using thinking routines to promote interactive learning environments on the academic results of tertiary education students enrolled in the Cost and Budgeting course at a Chilean higher education institution during 2016. Using the quasi‐experimental methodologies Propensity Score Matching and Differences in Differences, student grade averages and exam grade averages were compared using information from both the year this initiative was implemented (2016) and the previous year (2015) to control for preexisting differences between the comparison groups. The results show that students taught using thinking routines obtain better academic results than their counterparts taught using traditional methods.